Social programs and economic prospects for regional development (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
The purpose of this paper is to present the most relevant results of the assessment of a social program for education, implemented in Mexico City in 2007, still in force, which was designed, implemented and operated by the author Incentives Program is named for the Universal High School, Prep Yes this study suggests that development is a multidimensional process involving all sorts of factors that impact positively on social welfare and therefore calls on all areas social sciences to participate in their study of a coordinated manner, as the focus of study is located in society, present and future. This analytical framework allows to show that sustainable development, as well as concern for the environment, based on a principle of intergenerational equity also implies intragenerational equity, and therefore the solution must focus on welfare of inequalities that currently exist between social groups and regions. Also discussed briefly the methodological choices in the correct evaluation of social programs, with emphasis on the method known as the Logical Framework Matrix, which is the most widely accepted by the international promotion of development, and which was used to evaluate the program prepares Yes finally presents the results of the evaluation of the Yes Prep that describes the features of the program in terms of structure, coverage and operation, and displays the results of the evaluation its impact on: i) the income of the families of the beneficiaries; ii) the retention iii) the academic achievement of students, and iv) the expectations of the beneficiaries.
Keywords: social programs; marco logical; sustainable development